Análisis de transferencia de tecnología entre empresas asociadas - Porto Machado, Sabrina (2025)
Constantly questioning the role of institutionalization of interorganizational cost management in technology transfer of associate companies was the paper problem aiming at appraising the role of the institutionalization of interorganizational cost management in technology transfer of associate companies. Prior research studied financial and innovation performance focusing on how to manage stability and acquisition value project in firms. Such researches highlight the need for companies to improve technology transfer processes, which includes improving the cost management approach during technology change among firms. This is a qualitative, descriptive case study method with professionals in direction, management and coordination positions in a cooperative society, Central Sul/Sudeste and CAS as study subjects. The findings evidence a positive influence between technology implementation and exchange, highlighting the automation started by the process team in order to meet the associate needs and to improve operational efficiency. The research emphasizes the lack of a documentation standard, which makes process assessment difficult. It was observed that process institutionalization and effective collaboration are key to the successful transfer of technology. The lack of standardized documentation and the divergence of time and cost measurement evidence the need to improve interorganizational management.